1987
DOI: 10.1037/0097-7403.13.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Differential conditioning of the rabbit's nictitating membrane response to serial compound stimuli.

Abstract: Three experiments were conducted to determine the time course and contents of CS representations through an examination of differential conditioning of the rabbit's nictitating membrane response to two serial compounds. One compound (A-X+) was always paired with the unconditioned stimulus, and the other (B-X-) was always presented alone. All three experiments entailed manipulation of the interstimulus interval between the initial distinctive element of each compound (A and B) and the second, shared element (X)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
(86 reference statements)
1
33
1
Order By: Relevance
“…The appearance of CRs to the onset of the feature cue in both groups is consistent with the results of previous rabbit NM studies that have entailed the presentation of two conditioned stimuli (CSs) in sequence prior to the US (A®X+; Kehoe, Gibbs, Garcia, & Gormezano, 1979;Kehoe, Marshall-Goodell, & Gormezano, 1987;Kehoe et al, 2000;Schreurs, Kehoe, & Gormezano, 1993). The primary mechanism for the initial acquisition of CRs to a feature cue appears to be higher order conditioning between the A and the X stimuli (Gibbs, Cool, Land, Kehoe, & Gormezano, 1991;Kehoe, Feyer, & Moses, 1981).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The appearance of CRs to the onset of the feature cue in both groups is consistent with the results of previous rabbit NM studies that have entailed the presentation of two conditioned stimuli (CSs) in sequence prior to the US (A®X+; Kehoe, Gibbs, Garcia, & Gormezano, 1979;Kehoe, Marshall-Goodell, & Gormezano, 1987;Kehoe et al, 2000;Schreurs, Kehoe, & Gormezano, 1993). The primary mechanism for the initial acquisition of CRs to a feature cue appears to be higher order conditioning between the A and the X stimuli (Gibbs, Cool, Land, Kehoe, & Gormezano, 1991;Kehoe, Feyer, & Moses, 1981).…”
Section: Discussionsupporting
confidence: 78%
“…Real-time models assume that the cascade of stimulus elements diminishes over time, an assumption that real-time models share with older models that depict the temporal encoding of a stimulus as a decaying stimulus trace (Gormezano & Kehoe, 1981;Hull, 1943;Kehoe et al, 1987;Pavlov, 1927, p. 39;Sutton & Barto, 1981, 1990 or a short-term memory (Konorski & Lawicka, 1959;Riley, Cook, & Lamb, 1981;Roberts & Grant, 1976). For example, Buhusi and Schmajuk (1999) assume that the elements immediately following stimulus onset have a large magnitude but a short duration, whereas later elements are progressively smaller but have longer durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is only about 50 % generalization from tones to white noise (Kehoe & Napier, 1991). Second, the same tone and white noise used in this experiment have been used successfully in differential conditioning (Kehoe, Marshall-Goodell, & Gormezano, 1987). …”
Section: Discussionmentioning
confidence: 99%
“…In secondary conditioning, another conditioned stimulus C S2 is paired with C S1 until it, too, gains reinforcing properties. Various experiments have shown that the conditioned response to CS 2 can be adaptively timed (Gormezano and Kehoe, 1984;Kehoe, Marshall-Goodell, and Gormezano, 1987). Indeed, Gormezano and Kehoe (1984) claimed that, in their experimental paradigm, "first-and second-order conditioning follow the same laws" (p. 314), although they also acknowledged that some variables may differentially effect first-order and secondorder conditioning in other paradigms.…”
Section: The Problem Of Self-printing During Adaptively Timed Secondamentioning
confidence: 99%